2017
DOI: 10.1021/acs.jafc.7b00573
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Identification of eEF1A1 as a Molecular Target of Curcumol for Suppressing Metastasis of MDA-MB-231 Cells

Abstract: Curcumol, a major volatile component in Rhizoma Curcumae, exhibits a potent antimetastatic effect on breast cancer cells. However, its molecular mechanism remains poorly understood. In this study, we employed two-dimensional gel electrophoresis-based proteomics to investigate the cellular targets of curcumol in MDA-MB-231 cells and identified 10 differentially expressed proteins. Moreover, Gene Ontology analysis revealed that these proteins are mainly involved in nine types of cellular components, seven differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…Of note, the therapeutic value of EEF1A1 has been revealed in chronic lymphocytic leukemia, 38 hepatocarcinoma, 39 and breast cancer cells. 40 Our results exhibited the significant effect of silencing EEF1A1 on attenuating DLBCL growth both in vitro and vivo, thus providing experimental evidence for its further investigation…”
Section: Discussionsupporting
confidence: 61%
“…Of note, the therapeutic value of EEF1A1 has been revealed in chronic lymphocytic leukemia, 38 hepatocarcinoma, 39 and breast cancer cells. 40 Our results exhibited the significant effect of silencing EEF1A1 on attenuating DLBCL growth both in vitro and vivo, thus providing experimental evidence for its further investigation…”
Section: Discussionsupporting
confidence: 61%
“…Li identified that the promoter regulatory element of EEF1A1 was regulated by MALAT1 and over-expressed MALAT1 played an important role in the metastasis of BC ( 40 ). In addition, the decreased EEF1A1 expression via curcumol attributed to the suppression of BC metastasis ( 41 ). The function of S100B for inhibiting tumor migration was found in ER-negative BC and high expression of S100B was associated with better distant metastases-free survival in BC ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin (Cur) is a natural active substance extracted from the tubers of herbs such as Curcuma longa [ 1 ], Rhizoma zedoariae [ 2 ] and Radix curcumae [ 3 ], and it has broad application prospects in the fields of foods [ 4 , 5 ] and medicines [ 6 , 7 ]. It has a strong coloration ability and various physiological effects including anti-oxidation, anti-inflammation [ 8 ], anti-tumor [ 9 ], bacteriostasis, and promoting wound healing [ 10 ].…”
Section: Introductionmentioning
confidence: 99%